United with Christ in the spirit: The pneumatological dimension of the doctrine of justification. Issue 1 (4th December 2020) - Hegstad, Harald
Abstract: An important aspect of the consensus reached in the Joint Declaration on the Doctrine of Justification was the understanding of justification as union with Christ. From the Lutheran side, this understanding was dependent on the contributions of the Finnish school of Luther research. The Finns' understanding of justification has been criticized for its insufficient pneumatological basis, and this criticism might also be applied to the Joint Declaration. This article points to resources in Luther's theology as well as perspectives from Pentecostal theology that might contribute to developing the pneumatological dimension of the doctrine of justification.